Synergistic Suppression of DMBA-Induced Breast Cancer in Rats: Exploring the Preventive Potential of Diclofenac Sodium and D-Limonene Combination through mTOR Inhibition - Sankar, Srivarshini; Muthukaliannan, Gothandam Kodiveri (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: To examine the combination of Diclofenac sodium (DCF) and D-Limonene's (LIM) preventative effects against DMBA-induced breast cancer in a rat model. Materials and Methods: 7,12-Dimethylbenz[a]Anthracene (DMBA) was administered subcutaneously once to rats to trigger mammary cancer. DCF+LIM (DL) supplementation improved the level of antioxidants in mammary tissues, levels of lipids in serum, along with serum cytokines. The pathological alterations brought on by DL treatment were identified by a histological analysis of breast tissue, both malignant as well as normal. It was also investigated how DL impacted the mTOR gene as well as the build-up of the associated gene product. Results: PI3K/Akt/mTOR plays a critical role in cell metabolism and proliferation in both malignant and normal cell populations. Rats given DL treatment had lower levels of mTOR expression in their breast tissues, according to transcriptional and immunohistochemical investigations. Lastly, the results suggest that by blocking the mTOR pathway, DL can reduce tumor development in rats with breast cancer generated by DMBA. Conclusion: DMBA-induced breast cancer in rats showed a significant improvement in their preclinical chemoprevention capability when treated with a combination of diclofenac sodium and D-limonene, which inhibited the mTOR pathway.
Keywords: DMBA; Breast cancer; Diclofenac sodium; D-limonene; mTOR; Immunohistochemistry